2013
DOI: 10.2174/1874325001307010473
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Interventions Including Medical Injections for Neck Pain: An Overview as Part of the ICON Project

Abstract: Objectives:To conduct an overview (review-of-reviews) on pharmacological interventions for neck pain.Search Strategy:Computerized databases and grey literature were searched from 2006 to 2012.Selection Criteria:Systematic reviews of randomized controlled trials (RCT) in adults with acute to chronic neck pain reporting effects of pharmacological interventions including injections on pain, function/disability, global perceived effect, quality of life and patient satisfaction.Data Collection & Analysis:Two indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…In the ICON review [16] the authors found low quality evidence to support the use of IM-lidocaine for chronic MND, and epidural methylprednisolone with lidocaine injection for radiculopathy. There was a lack of evidence for the effectiveness of different types of corticosteroids and local anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ICON review [16] the authors found low quality evidence to support the use of IM-lidocaine for chronic MND, and epidural methylprednisolone with lidocaine injection for radiculopathy. There was a lack of evidence for the effectiveness of different types of corticosteroids and local anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…A 2011 systematic review on botolinum toxin (BoNT) for subacute/chronic neck pain was updated [15] (search end date 2010) and the conclusions were consistent with an International Collaboration on Neck (ICON) overview of systematic reviews on medicines and injections for neck pain [16] in suggesting that there is evidence against the use of BoNT-A for chronic neck pain or subacute/chronic whiplash. Further the ICON review of systematic reviews gave evidence against medial branch block with steroids for chronic facet joint pain, but for the use of eperison hydrochloride for chronic neck pain.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Since the majority of new cases of neck pain can be managed with a stay active approach, and a substantial minority are at risk of transitioning into adverse outcomes, it is essential that appropriate management include selection and timing. While systematic reviews and overviews published in this special issue indicate a wealth of evidence [12-16], that information is imperfect and poorly implemented. Neck pain interventions typically demonstrate small to modest effects, with neck pain successfully rehabilitated in comparison to other orthopedic disorders [17].…”
Section: The Knowledge To Action Gapmentioning
confidence: 99%
“…Nonsteroidal antiinflammatory drugs (NSAIDs) could relieve pain as firstline agents in acute settings [7]. The efficacy of ibuprofen in the treatment of cervical nerve root pain has also been reported [8], but it can only relieve pain and has no effect on the other symptoms of CSR.…”
Section: Introductionmentioning
confidence: 99%